Conserving unprotected important sites for shorebirds on China's coasts. Issue 2 (15th February 2022) - Duan, Houlang; Yu, Xiubo; Xia, Shaoxia; Liu, Yu
Abstract: The loss of natural wetland habitats along China's coasts has contributed to population declines in waterbirds, especially migratory shorebirds. Identifying important shorebird sites is important for habitat conservation and management. We integrated shorebird survey datasets from multiple sources (bird‐watching websites, survey reports, and published literature) for coastal wetlands in China and used the criterion of 1% of the global or flyway population (hereafter, Ramsar 1% criterion) and priority index P i to identify conservation priority sites and corresponding prioritization rank. We used gap analysis to identify the conservation status of natural protected areas. Forty‐eight conservation priority sites, where 31 shorebird species met the Ramsar 1% criterion. The prioritization rank was very high priority for six sites, high priority for five sites, and priority for 37 sites. There were 28 conservation priority sites for shorebirds with conservation gaps, and these accounted for 58.33% of all 48 conservation priority sites. Of these unprotected sites, the prioritization ranks were very high priority or high priority for six sites, which were mainly concentrated in Jiangsu province. We recommend prioritizing the protection of these sites by creating new protected areas or incorporating these areas into the existing system.